Antibiotic-Loaded Bone Cement in Prevention of Periprosthetic Joint Infections in Primary Total Knee Arthroplasty: A Register-based Multicentre Randomised Controlled Non-inferiority Trial (ALBA trial). Issue 1 (28th January 2021) - Leta, Tesfaye H; Gjertsen, Jan-Erik; Dale, Håvard; Hallan, Geir; Lygre, Stein Håkon Låstad; Fenstad, Anne Marie; Dyrhovden, Gro Sævik; Westberg, Marianne; Wik, Tina Stromdal; Jakobsen, Rune Bruhn; Aamodt, Arild; Röhrl, Stephan Maximillian; et al.
Abstract : Introduction: The current evidence on the efficacy of antibiotic-loaded bone cement (ALBC) in reducing the risk of periprosthetic joint infections (PJI) after primary joint reconstruction is insufficient. In several European countries, the use of ALBC is routine practice unlike in the USA where ALBC use is not approved in low-risk patients. Therefore, we designed a double-blinded pragmatic multicentre register-based randomised controlled non-inferiority trial to investigate the effects of ALBC compared with plain bone cement in primary total knee arthroplasty (TKA). Methods and analysis: A minimum of 9, 172 patients undergoing full-cemented primary TKA will be recruited and equally randomised into the ALBC group and the plain bone cement group. This trial will be conducted in Norwegian hospitals that routinely perform cemented primary TKA. The primary outcome will be risk of revision surgery due to PJI at 1-year of follow-up. Secondary outcomes will be: risk of revision due to any reason including aseptic loosening at 1, 6, 10 and 20 years of follow-up; patient-related outcome measures like function, pain, satisfaction and health-related quality of life at 1, 6 and 10 years of follow-up; risk of changes in the microbial pattern and resistance profiles of organisms cultured in subsequent revisions at 1, 6, 10 and 20 years of follow-up; cost-effectiveness of routine ALBC versus plain bone cement use in primary TKA. We will use 1:1 randomisation with random permuted blocks and stratify by participating hospitals to randomise patients to receive ALBC or plain bone cement. Inclusion, randomisation and follow-up will be through the Norwegian Arthroplasty Register. Ethics and dissemination: The trial was approved by the Western Norway Regional Committees on Medical and Health Research Ethics (reference number: 2019/751/REK vest) on 21 June 2019. The findings of this trial will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: NCT04135170 .